The students' perception on the use of computer assisted language learning - Kartika Marta Budiana (Politeknik Negeri Bali, 2021)
While listening comprehension is the heart of language, but it is the least understood and researched skill. This is the reason why particular attention must be given to listening comprehension as a skill required in foreign language acquisition and especially in part played by listening skills. This study aims to see the effect of computer assisted language learning (CALL) applied to students` listening performance. This study adopts a qualitative approach. Data were collected using questionnaires. The findings in this study reveals Students`-perceptions and feedback on CALL. It shows that many of the students feel easier in understanding the listening material using CALL. It also shows that many of the teachers interested using CALL but not interested with the LMS provided. It can be concluded that most of the students have a positive impression about the use of CALL in English learning, especially for Listening.